Remodeling in the Prefrontal Cortex of a Brain-related to Higher Executive Functions in Adolescence: Its effects on Behavior - Tin, Moe Nwe; San, San Aye; Khin, Than Yee; Soe, Lwin; Bhagat, Vidya (Research Journal of Pharmacology and Pharmacodynamics, 2021)
Adolescence is a critical stage of the developmental trajectory, where a child’s transition to independent living may result in lead healthy or unhealthy styles. During this period, it is easier to mend an individual as a healthy adult; at the same time, misguided children may enter into risky behaviors. The aim of the study to get an insight into changing brains of adolescents and their behavioral outcomes. The current review search engine proceeds with reviewing the literature in the past through electronic databases such as PubMed, Medline, and Scopus databases using keywords such as adolescent stage, the brain of teenagers, risk behaviors, reduction in gray matter in the prefrontal cortex. The current study reviewed and analyzed 20 articles. The reviewed articles would increase the awareness and insights regarding brain changes and their behavioral outcomes. This insightful information’s drawn out of the study may help professionals and parents who intervene in the adolescent’s problem behaviors.